2018
DOI: 10.1016/j.spinee.2018.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in spine surgery—a systematic integrative review

Abstract: Five categories of interacting factors that influenced symptoms of anxiety and depression both before and after surgery were identified: pain, lack of information, disability, return to work, and mental health. Information appears to have a regulating effect on anxiety and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 63 publications
3
97
0
2
Order By: Relevance
“…29 Moreover, an integrative review by Strøm et al highlighted the prevalence and challenges faced by providers and surgeons in treating spine surgery patients with anxiety and depression. 39 Smoking status has also been shown to adversely affect outcomes. Crawford et al, in their analysis of 7207 patients undergoing lumbar spine surgery, found that smokers were less likely to be satisfied than nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…29 Moreover, an integrative review by Strøm et al highlighted the prevalence and challenges faced by providers and surgeons in treating spine surgery patients with anxiety and depression. 39 Smoking status has also been shown to adversely affect outcomes. Crawford et al, in their analysis of 7207 patients undergoing lumbar spine surgery, found that smokers were less likely to be satisfied than nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…The perception of pain in relation to spinal surgery can be altered by external factors, and psychosocial characteristics related to different degrees of clinical impairment and quality of life in the preoperative period may influence surgical recovery [5]. For example, patients with chronic and disabling symptoms may experience symptoms of anxiety and depression, which are important outcome predictors of physical impairment, pain and lower health-related quality of life [6,7,8]. Factors associated with anxiety and depression both before and after spine surgery are reported to be a greater experience of pain, the need for information, the degree of self-reported disability, employment status (feelings of not being able to contribute to society) and mental health status [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients with chronic and disabling symptoms may experience symptoms of anxiety and depression, which are important outcome predictors of physical impairment, pain and lower health-related quality of life [6,7,8]. Factors associated with anxiety and depression both before and after spine surgery are reported to be a greater experience of pain, the need for information, the degree of self-reported disability, employment status (feelings of not being able to contribute to society) and mental health status [8]. The need for information is reported to be a significant theme amongst qualitative studies from spinal surgery, with patients expressing a need for individualized information given in sufficient quantities and at the appropriate time [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor outcome appears to be associated with a number of complex elements, including psychological responses such as fear and anxiety (8). Evidence suggests that many patients undergoing lumbar spine surgery may suffer from central sensitization, depression, anxiety, and poor coping strategies (9,10).…”
Section: Introductionmentioning
confidence: 99%